The Void of Mies: Unfolding Unbuilt Projects of Mies van der Rohe - Hanada Kazu Blumfeld (Technical Transactions, 2025)
The core of Mies van der Rohe still remains as a vast void. Since the Friedrichstrasse Skyscraper Project in 1921, Mies’s manifestos have always been mediated to the world through the unbuilt projects. In Mies’s planes, there is a dialectic between the manifesto and the realized works in the unbuilt projects, which complement each other’s dimensions, and only in this way can Mies the architect be historicized. However, upon examining the unbuilt projects in detail, hidden qualities have been uncovered that have not yet been recognized by historians and critics. Thus far, more than 35 unbuilt projects have been analyzed academically, both known and unknown, creating hypothetical spaces in the form of drawings, 3D modeling, and physical models. The unexplored qualities that have emerged in this process are, in short, the phenomenological manifestation of space and Mies’s particular view of nature, as well as the spiritual boundaries that lie behind these planes of perception.